(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Family prosperity and personal growth are both dependent on marital contentment. Women’sroles in the economy and society have grown in prominence as the country has progressed. Theelements that influence women’s marital satisfaction are investigated in this study. Occupational status(working or non-working), family type (nuclear or joint), place of settlement (urban and rural), education,age, personal income, and number of children are among the influences. The data for the study wasacquired from 50 women in (Jaipur) Rajasthan using a survey research approach. The married women’smarital satisfaction was tested using an independent samples t-test based on their employment status(working or non-working), family type (nuclear or joint), and site of residence (urban or rural). Thefindings show a considerable difference in marital happiness between working and non-working women.Women who do not work are shown to be happier in their marriages. There is no variation in maritalhappiness among groups depending on family type or settlement location. The researchers utilized aone-way ANOVA to examine the variations in marital happiness based on age, education, personal icome, and the number of children. The findings reveal that marital happiness varies greatly de spendingon education and career. There is no difference in marital happiness based on age, wealth, or thenumber of children. Both women’s and men’s education has a considerable impact on maritalsatisfaction, demonstrating that education improves married life. Job satisfaction leads to maritalhappiness, which has a favorable influence on organizational performance. As a result, given theimportance of women in the labour force in the country’s economic and social growth, this study advisesthat policymakers explore improving the working environment in order to boost working women’s maritalhappiness.